THE TRADING SPACE IN INPRES MARKET OF LHOKSEUMAWE CITY (STUDY OF BEHAVIOUR ASPECT) (Talenta Publisher, 2018)
This research was begun from the phenomena of the use of unlimited space at Pasar Inpres in Lhokseumawe. The behavior of using space which intervene public space for personal interest is called territoriality behavior. The objective of this research was to find out the influence of human territoriality behavior on setting as the interaction between market users and their activity space. Territoriality is emphasized on personalization, labeling, domination, and control. This research used descriptive qualitative method with rationalistic approach. The data were gathered by conducting field observation, based on human behavior and supported by behavior mapping. The conclusion of the research is that territoriality behavior, based on personalization, tends to familiarity among territory owners. Territoriality based on labeling leads to one’s behavior in labeling his territory into three forms. Besides that, based on domination, it leads to the behavior of using public facility, roads which is used for parking lot and for selling place which influence the circulation of market users. Meanwhile, territoriality behavior, based on control, can be seen in the used elements, either they are massive or not, and in the form of the owners in maintaining their territory.